PENGARUH GAYA HIDUP, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU AEROSTREET: (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2021 Universitas Bhayangkara Jakarta Raya) - Riyanto, Ridho; Nursal, Fadhli; Sumantyo, Franciscus Dwikotjo Sri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of consumer lifestyle, brand image, and product quality on purchasing decisions for Aerostreet shoes, using a case study of students from the 2021 cohort of the Management Study Program at Universitas Bhayangkara Jakarta Raya. A quantitative research approach was employed, with data collected through questionnaires using purposive sampling. The study involved 171 respondents. Data analysis was conducted using the Partial Least Square (PLS) method with the assistance of SmartPLS 4.0 software. The results show that consumer lifestyle and product quality have a positive and significant effect on purchasing decisions, while brand image has no significant effect. These findings suggest that marketing strategies focusing on consumer lifestyle and improving product quality are more effective in influencing purchasing decisions for Aerostreet shoes.